Formation of broad domain boundary during dot ion beam irradiation in SBN:Ni single crystals. Issue 1 (19th May 2022) - Shikhova, V. A.; Slautina, A. S.; Chezganov, D. S.; Nebogatikov, M. S.; Akhmatkhanov, A. R.; Turygin, A. P.; Ivleva, L. I.; Shur, V. Ya.
Abstract: Formation of the circular-shaped isolated domains surrounded by broad domain boundary (BDB) during dot ion beam irradiation in SBN:Ni crystals with submicron domain structure was studied. It was shown that domain and BDB sizes and depths increased proportionally to a square root of the irradiation dose. The radius decreased and BDB width increased with depth for dot and 2 D array exposure. The observed abnormal domain structure evolution was attributed to equiprobable positions of the steps due to merging with nanodomains. BDB increase with depth was explained by the features of spatial distribution of field polar component in the bulk.